New Expandable Hydrogel-Platinum Coil Hybrid Device for Aneurysm Embolization - Kallmes, David F.; Fujiwara, Naomi H. (American Journal of Neuroradiology, 2002)
Summary: This study introduces a new, hybrid embolic device that in addition to offering all the important attributes of existing detachable platinum coils also shows an enhanced ability to fill aneurysm cavities. The device consists of a carrier platinum coil coupled to an expandable hydrogel material, which undergoes a ninefold increase in volume when placed into a physiological environment. Distinct from previous devices aimed at speeding the organization of thrombus, the new device has been designed to entirely fill the aneurysm cavity, with complete or near-complete exclusion of thrombus. Unlike thrombus, the hydrogel material is stable and unaffected by natural thrombolytic processes and thus may diminish observed rates of aneurysm recanalization. We report the angiographic and histologic findings of the new, hybrid device used to treat experimental aneurysms in rabbits.